A complex variable boundary point interpolation method for the nonlinear Signorini problem. (15th June 2020) - Li, Xiaolin; Li, Shuling
Abstract: A complex variable boundary point interpolation method (CVBPIM) is presented for numerical analysis of the nonlinear Signorini problem. To reduce the computational cost and to improve the stability of the point interpolation method, a complex variable point interpolation method (CVPIM) is developed to construct meshless shape functions with interpolation properties. By using a projection technique to deal with the nonlinear inequality boundary conditions, and combining boundary integral equations with the CVPIM to establish discrete linear algebraic systems, the CVBPIM is an easy-to-implement and boundary-only meshless method for nonlinear Signorini problems. Numerical results are presented to show the accuracy and efficiency of the method.